Boganmeldelser - Hans Klette; Anette Storgaard; Mikaela Heikkilä; Anders Nilsson; Helene Oppen Gundhus; Jens Evald; Thomas Elholm; Hanns von Hofer; Hedda Giertsen (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews